The Study of River Water Quality in Water Pollution Control: Case Study of Talawaan River, North Minahasa District, North Sulawesi Province - Alfa Winny Pongoh; Fadillah Putra; Soemarno (Indonesian Journal of Environmental Management and Sustainability, 2021)
This research was conducted to assess the quality of river water in the context of controlling water pollution in the Talawaan River in North Minahasa Regency, North Sulawesi Province. This research is a descriptive-quantitative research. The field research was carried out in the Talawaan River, North Minahasa Regency. Water quality measurement includes physical parameters: TSS, and chemical parameters; BOD and COD were carried out at five monitoring points. The results showed that the content of BOD, COD, and TSS in Talawaan River water met the water quality standards (Type B water). The characteristics of the waste (BOD, COD and TSS), the concentration values of BOD, COD and TSS concentration values do not exceed the quality standard according to their designation. The potential for domestic waste pollution load reaches 1,495 kg/day from a total population of 16,040 people. The status of Telawan River water quality is classified as ”lightly polluted” based on the studied parameters; there are several other variables that were not included in this study, such as T-P, Total Coli, and Fecal Coli.